(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Inhalational induction of anaesthesia remains of fundamental technique in paediatric anaesthesia. Halothane used most frequently for inhalational induction in children. Halothane is not an ideal induction agent because of its potential to cause bradycardia, hypotension and ventricular ectopy. The pleasant nonpungent order of sevoflurane, faster induction of anaesthesia and stable vital signs during induction suggest that it may be a suitable alternative to halothane for use in paediatric anaesthesia. Objectives The aim of study is to compare the induction time and haemodynamic response during induction of sevoflurane and halothane. Methods A total number of 60 patients, age within 1-12 years (ASA grade I & II) were selected randomly into two groups, thirty in each group. Group A induction was done by halothane and Group B induction was done by sevoflurane. Anaesthesia was induced with 60% N2O and 40% O2 and starting inspired concentration of halothane was 1% or sevoflurane was 2% followed by stepwise increases in the inspired concentrations of either sevoflurane (1.5-2% increments) or halothane (0.5-1% increments) every three to four breath until the patients no longer blinked in response to touching the eye lashes. Arterial pressure, heart rate, oxygen saturation (SPO2) were recorded every minute for 3 minutes during induction and induction time was recorded. Results Induction time was significantly shorter in the sevoflurane group compared to the halothane group (P < 0.001). In haemodynamic profile heart rate and mean arterial pressure were significantly reduced in halothane group while no significant changes were observed in sevoflurane group during induction period (P < 0.001). Conclusion The study concludes that induction of anaesthesia was faster with sevoflurane than halothane. Vital signs were stable with sevoflurane during induction period. DOI: http://dx.doi.org/10.3329/jbsa.v24i1.19794 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(1): 13-17